A paz nos instrumentos de organização da informação: uma análise dos conceitos de paz e guerra, da cultura de paz e dos estudos para a paz na Classificação Decimal Dewey - Rizzi, Iuri Rocio Franco [UNESP] (2008)
It is treated of a study concerning the systems of bibliographical classification, specifically the Dewey Decimal Classification (DDC), one of the instruments of Knowledge Organization more used in generalists libraries in Brazil and in the world. Recent studies have been demonstrating that such instruments are not neutral in relation to values and cultural aspects. Such instruments are investigated to the light of a second theme, the peace, and it comprises the recent progress in the peace concept and their unfoldings in the theoretical and practical fields: the area of Peace Research and the Culture of Peace movement. It has as objective to verify and to analyze the treatment given to the theme of the peace in DDC. Specifically, it was looked for to verify and to analyze the peace concepts, the movement denominated Culture of Peace and the theoretical field Studies for Paz in the 21st and 22nd editions of the Dewey Decimal Classification. These propositions intend to answer to the following questions: is it DDC capable to work appropriately with the organization of documents whose contents refer, first, to the peace concept, in its general meaning; second, to the Peace Research field; and, third, to Culture of Peace Movement? It is discussed, still, the relationship of mutual influence between the societies and the bibliographical classifications. It's about theoretical and exploratory research, due to the objectives and to the approach of the themes proposed. The methodological and technical procedures of research used were the bibliographical review and the documental analysis. The analysis of the data confirmed the initial hypothesis that the Dewey Decimal Classification is not capable to work with themes relatives to the peace concept, to social movement denominated Culture of Peace and to the Peace Research field. Finally, it is considered that the Dewey Decimal Classification... (Complete abstract click electronic access below)